2018
DOI: 10.2478/ijme-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement and performance: a systematic literature review

Abstract: Scholars and practitioners indicate that low level of employee engagement at work is currently one of the most alarming global economic problems. The potential consequence of this phenomenon is declining work performance. Therefore, it becomes important to understand the concept of work engagement, its meaning for employees, and implications for employers. The article is a systematic review of the body of literature, presenting the results of research on the association between employee engagement and various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 87 publications
5
74
0
2
Order By: Relevance
“…The outcomes of an organization depend on the employees' performances [10,11]. Therefore, a strategic approach is essential to the business, because in the long term, if the activities planned by managers have the expected outcomes, they will lead to better performance [12,13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outcomes of an organization depend on the employees' performances [10,11]. Therefore, a strategic approach is essential to the business, because in the long term, if the activities planned by managers have the expected outcomes, they will lead to better performance [12,13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, greater overall satisfaction levels of employees are also outcomes of employee engagement (Jeung, 2011). Different studies found that high engagement levels lead to greater task performance (Motyka, 2018) Hammoud, 2017). Consequently, Da Costa and Loureiro (2019) argue that engaged employees are more likely to contribute to a better consumer experience through higher quality standards.…”
Section: Outcomes Of Employee Engagementmentioning
confidence: 99%
“…They do not perform well and demotivate or discourage the organization's performance. The academic community also sees the problem of low employee engagement and its negative impact on business outcomes (Motyka. B., 2018).…”
Section: Background Of the Studymentioning
confidence: 99%